已知E(x)=2,D (x)=1,y=x2,则E(y)的值为( ),
A: 5
B: 2
C: 1
D: 20
A: 5
B: 2
C: 1
D: 20
举一反三
- 已知E(X)=2,E(Y)=2,E(XY)=5,则X,Y的协方差Cov(X,Y)=( )。 A: 1 B: 0 C: -1 D: 4
- 已知齐次方程$(x-1){{y}^{''}}-x{{y}^{'}}+y=0$的通解为$Y={{C}_{1}}x+{{C}_{2}}{{e}^{x}}$,则方程$(x-1){{y}^{''}}-x{{y}^{'}}+y={{(x-1)}^{2}}$的通解是( ) A: ${{\text{C}}_{1}}x+{{\text{C}}_{2}}{{e}^{x}}-({{x}^{2}}+1)$ B: ${{\text{C}}_{1}}x+{{\text{C}}_{2}}{{e}^{x}}-({{x}^{3}}+1)$ C: ${{\text{C}}_{1}}x+{{\text{C}}_{2}}{{e}^{x}}-{{x}^{2}}$ D: ${{\text{C}}_{1}}x+{{\text{C}}_{2}}{{e}^{x}}-{{x}^{2}}+1$
- 已知\( y = \ln (1 + {x^2}) \),则\( y' \)为( ). A: \( { { 2x} \over {1 + {x^2}}} \) B: \( {x \over {1 + {x^2}}} \) C: \( {1 \over {1 + {x^2}}} \) D: \( { { {x^2}} \over {1 + {x^2}}} \)
- 已知X, Y独立, E(X)= E(Y)=2, E(X2)=<br/>E(Y2)=5, D(3X-2Y)=( ). A: 3 B: 1 C: 13 D: 5
- 已知x=1,y=2,z=3,执行下列语句if(x>y) z=x;x=y;y=z;则x,y,z的值分别是 A: x=1,y=2,z=3 B: x=2,y=3,z=1 C: x=2,y=2,z=1 D: x=2,y=3,z=3